Step
*
2
of Lemma
near-inverse-of-increasing-function
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. ∀[d:ℕ]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ d)) 
       supposing a < b
⊢ ∀a,b:ℤ.
    ∀k:ℕ+
      (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
         ((z ≤ f[(r(b))/k]) and 
         (f[(r(a))/k] ≤ z) and 
         (∀x,y:ℝ.
            (((r(a))/k ≤ x)
            
⇒ (x < y)
            
⇒ (y ≤ (r(b))/k)
            
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n)))))))) 
    supposing a < b
BY
{ Auto }
1
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. ∀[d:ℕ]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ d)) 
       supposing a < b
6. a : ℤ
7. b : ℤ
8. a < b
9. k : ℕ+
10. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
11. f[(r(a))/k] ≤ z
12. z ≤ f[(r(b))/k]
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
Latex:
Latex:
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  n  :  \mBbbN{}\msupplus{}
3.  M  :  \mBbbN{}\msupplus{}
4.  z  :  \mBbbR{}
5.  \mforall{}[d:\mBbbN{}]
          \mforall{}a,b:\mBbbZ{}.
              \mforall{}k:\mBbbN{}\msupplus{}
                  (\mexists{}c:\mBbbZ{}
                      (\mexists{}j:\mBbbN{}\msupplus{}  [((|f[(r(c))/j]  -  z|  \mleq{}  (r1/r(n)))
                                    \mwedge{}  ((r(a))/k  \mleq{}  (r(c))/j)
                                    \mwedge{}  ((r(c))/j  \mleq{}  (r(b))/k))]))  supposing 
                        ((z  \mleq{}  f[(r(b))/k])  and 
                        (f[(r(a))/k]  \mleq{}  z)  and 
                        (\mforall{}x,y:\mBbbR{}.
                              (((r(a))/k  \mleq{}  x)
                              {}\mRightarrow{}  (x  <  y)
                              {}\mRightarrow{}  (y  \mleq{}  (r(b))/k)
                              {}\mRightarrow{}  ((f[x]  \mleq{}  f[y])  \mwedge{}  (((y  -  x)  \mleq{}  (r1/r(M)))  {}\mRightarrow{}  ((f[y]  -  f[x])  \mleq{}  (r1/r(n)))))))  and 
                        (((M  *  (b  -  a))  -  k)  \mleq{}  d)) 
              supposing  a  <  b
\mvdash{}  \mforall{}a,b:\mBbbZ{}.
        \mforall{}k:\mBbbN{}\msupplus{}
            (\mexists{}c:\mBbbZ{}
                (\mexists{}j:\mBbbN{}\msupplus{}  [((|f[(r(c))/j]  -  z|  \mleq{}  (r1/r(n)))
                              \mwedge{}  ((r(a))/k  \mleq{}  (r(c))/j)
                              \mwedge{}  ((r(c))/j  \mleq{}  (r(b))/k))]))  supposing 
                  ((z  \mleq{}  f[(r(b))/k])  and 
                  (f[(r(a))/k]  \mleq{}  z)  and 
                  (\mforall{}x,y:\mBbbR{}.
                        (((r(a))/k  \mleq{}  x)
                        {}\mRightarrow{}  (x  <  y)
                        {}\mRightarrow{}  (y  \mleq{}  (r(b))/k)
                        {}\mRightarrow{}  ((f[x]  \mleq{}  f[y])  \mwedge{}  (((y  -  x)  \mleq{}  (r1/r(M)))  {}\mRightarrow{}  ((f[y]  -  f[x])  \mleq{}  (r1/r(n)))))))) 
        supposing  a  <  b
By
Latex:
Auto
Home
Index